Quadrennial Defense Review Report: A mixed picture - Benjamin Schreer (Stiftung Wissenschaft und Politik (SWP), 2006)
The Pentagon's new Quadrennial Defense Review (QDR) is a comprehensive review of U.S. defense strategy, force structure, transformation plans, and budget. From a European perspective two main points are of particular interest. First, U.S. forces are focusing on worldwide deployments in the long war against international terrorism. Second, an ever greater shift towards the Asia-Pacific region is taking place in the emergence of a rising China. As a consequence, non-European allies and partners are of increasing importance in a new U.S. concept of 'global partnerships.' Europe needs to adapt to this strategic reality. (SWP-Comments / SWP)
Keywords: 320